Structural bases for blockade and activation of BK channels by Ba2+ ions - Srivastava, Shubhra; Miranda, Pablo; Giraldez, Teresa; Zhu, Jianghai; Cachau, Raul E.; Holmgren, Miguel (Frontiers in Molecular Biosciences, 2024)
We studied the impact of Ba2+ ions on the function and structure of large conductance potassium (BK) channels. Ion composition has played a crucial role in the physiological studies of BK channels due to their ability to couple ion composition and membrane voltage signaling. Unlike Ca2+, which activates BK channels through all Regulator of K+Conductance (RCK) domains, Ba2+ has been described as specifically interacting with the RCK2 domain. It has been shown that Ba2+ also blocks potassium permeation by binding to the channel’s selectivity filter. The Cryo-EM structure of the Aplysia BK channel in the presence of high concentration Ba2+ here presented (PDBID: 7RJT) revealed that Ba2+ occupies the K+ S3 site in the selectivity filter. Densities attributed to K+ ions were observed at sites S2 and S4. Ba2+ ions were also found bound to the high-affinity Ca2+ binding sites RCK1 and RCK2, which agrees with functional work suggesting that the Ba2+ increases open probability through the Ca2+ bowl site (RCK2). A comparative analysis with a second structure here presented (PDBID: 7RK6), obtained without additional Ba2+, shows localized changes between the RCK1 and RCK2 domains, suggestive of coordinated dynamics between the RCK ion binding sites with possible relevance for the activation/blockade of the channel. The observed densities attributed to Ba2+ at RCK1 and RCK2 sites and the selectivity filter contribute to a deeper understanding of the structural basis for Ba2+'s dual role in BK channel modulation, adding to the existing knowledge in this field.